Bit-error-rate Optimization for CDMA Ultra-wideband System Using Generalized Gaussian Approach - Chung Gwo Chin; Mohamad Yusoff Alias; Tiang Jun Jiat (Institute of Advanced Engineering and Science, 2017)
Ultra-wideband is a wireless technology arisen for future high speed multimedia applications. It can provide data rate in excess of Gigabits per second by transmitting impulse signal through the free space. However, the ultra-wideband indoor channel models proposed by the IEEE P802.15.3a suffer long multipath propagation. Due to this multipath effect, several studies have been done to improve the bit-error-rate performance of the ultra-wideband system in the existence of severe interference. Yet, most of the proposed algorithms were formulated based on the Gaussian distribution, which is not true in ultra-wideband. In this paper, we first analyze the statistical behavior of the CDMA-UWB signal by applying the Kullback-Leibler divergence index. Based on the analysis, a non-Gaussian equalizer is developed by deriving an enhanced bit-error-rate optimization algorithm using the Generalized Gaussian approach. The proposed equalizer has been shown to achieve a performance gain of at least 1.5dB to 2dB over the other equalizers simulated under IEEE P802.15.3a channel models.